STUDY OF PRODUCTIVE PERFORMANCE OF THREE VARIETIES OF JAPANESE QUAIL IN MEAT PRODUCTION* - Hassan, Khalid Hamid; Abd- Alsattar, Ali Rafea (Diyala Agricultural Sciences Journal, 2017)
The study was conducted at the poultry farm in the Department of Animal Resources - College of Agriculture - University of Diyala during the Autumn season of 2014, to determine and compare the productive performance of the three varieties of Japanese quail : black, white and brown, under the local natural environmental conditions in Iraq. Used in the study, 329 one day chicks belong to the three varieties, and the experiment was designed according to the Completely Randomized Design ( CRD ) with three replicates for each variety. Measurements were recorded for the following traits: The weight of the chick at hatching, weekly live body weight, weekly weight gain, weekly feed intake, and feed conversion efficiency. The results showed a highly significant (P <0.01) superiority of black variety in live body weight, compared with white and brown varieties at ages 1, 2 and 3 weeks, furthermore, the results recorded that this superiority has vanished at the age of 6 weeks, therefore, the body weight of black, white and brown varieties at 6 weeks of age became 179.69, 171.65 and 175.88 g respectively. The results recorded that there is a high significant superiority in feed consumption of the black variety with compare to other varieties in the weeks 1, 2 and 6 weeks. Black variety superiority on the white variety in the feed conversion during the first four weeks was also observed. The results indicated that weight gain is becoming very few in the seventh week, which indicates to select the age of 6 weeks as a market age.